Mixed Legionella pneumophila Serogroup Infection in a Single Patient: Case Report and Literature Review - Bram Vanmechelen; Fedoua Echahidi; Stijn Jonckheere; Patricia Vandecandelaere; Ines Malysse; Oriane Soetens; Charlotte Michel (Infectious Disease Reports, 2026)
Background: Legionnaires’ disease (LD) is most often described as caused by a single Legionella pneumophila (Lp) serogroup (SG), typically SG1. However, mixed infections involving multiple SGs or even different Legionella species can occur within a single host. Such cases remain underrecognized and pose challenges for diagnosis, clinical management, and outbreak investigation. Case presentation: A 61-year-old woman developed acute fever, malaise, and productive cough after visiting a wellness spa in France, with radiological findings consistent with a lower respiratory tract infection. The urinary antigen test (UAT) for Lp was negative, but respiratory multiplex PCR was weakly positive. Subsequent testing at the Belgian National Reference Centre (NRC) for Legionella revealed an unexpected discordance between an in-house SG1-specific PCR and culture-based findings. Further analysis identified co-infection with two distinct Lp strains, SG1 (sequence type, ST146) and SG10 (ST1267), using a combination of direct sequence-based typing (SBT) and culture with serogrouping of multiple colonies. The patient improved rapidly after treatment with oral levofloxacin. Conclusions: Mixed Lp SG infections are likely underrecognized in routine practice, as neither UAT, commercial molecular assays, nor characterization of a single cultured isolate may adequately capture within-host strain diversity. Comprehensive diagnostic approaches combining culture with analysis of multiple colonies and molecular tests are essential for accurate case detection and source attribution. Referral to NRCs is recommended when advanced typing methods are unavailable. This first reported Belgian case illustrates the potential implications for patient management and epidemiological investigations, underscoring the need for broader diagnostic strategies.